1998
DOI: 10.1080/00071669889222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementing the hen's diet with vitamin A on the accumulation of vitamins A and E, ascorbic acid and carotenoids in the egg yolk and in the embryonic liver

Abstract: 1. The effect of a range of supplementations of vitamin A to the laying hen on the concentration of vitamins A, E, ascorbic acid and carotenoids in the maternal liver, the egg yolk and the embryonic liver were investigated. 2. Four groups of 25 Rhode Island Red hens were fed on standard layer-breeder diets with concentrations of supplemented vitamin A ranging from 0 to 120 micrograms/g retinol equivalents from 28 weeks of age. After 3 months, the concentration of vitamin A in the maternal liver was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
42
1
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 45 publications
7
42
1
5
Order By: Relevance
“…Therefore laying hens may infl uence phenotypic development of their progeny not only by providing basic genetic information but also by depositing nutrients and biologically active substances into their eggs. It is well known that lipid soluble vitamins and antioxidants are necessary for successful embryonic development, including posthatching growth, health status and future performance of hatchlings (Surai et al 1998;Karadas et al 2005). Current research is focused on maternal hormones as other signifi cant components of egg yolk that may substantially affect an ability of offspring to cope with their environment .…”
mentioning
confidence: 99%
“…Therefore laying hens may infl uence phenotypic development of their progeny not only by providing basic genetic information but also by depositing nutrients and biologically active substances into their eggs. It is well known that lipid soluble vitamins and antioxidants are necessary for successful embryonic development, including posthatching growth, health status and future performance of hatchlings (Surai et al 1998;Karadas et al 2005). Current research is focused on maternal hormones as other signifi cant components of egg yolk that may substantially affect an ability of offspring to cope with their environment .…”
mentioning
confidence: 99%
“…In this study, the retinol content of the egg yolk was determined to increase in the groups with R-palmitate and R-acetate supplementation by 66.2% and 32.1%, respectively, in the first month, and 51.4% and 46.2%, respectively, in the second month (Table 6). Some studies also reported an increase in the retinol content in the egg yolk with retinol (26) and R-acetate supplementation of hen diets (10,11,23). Depending on the forms (12) and the levels (23) of vitamin A in the diet, the liver plays an important role as a regulator of this vitamin's metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of dietary nutrients or feed additives has been reported to affect the egg yolk MDA concentration in many studies (29,30). Similarly, it has also been noted that the retinol content in the egg yolk prevents lipid oxidation; vitamin A, which can be found in an adequate amount in the egg yolk, must be added into diets to activate this protective effect, and vitamin A acts as an antioxidant by passing directly into the yolk (23). Thus, in the 8th week of this study, egg retinol levels exhibited a significant increase in the retinol, R-acetate, and R-propionate groups and a slight but nonsignificant increase in the R-palmitate group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pigments can be natural vegetable compounds such as xanthophyls (oxygen derivatives of carotenoids). Because of their low stability, natural pigments (Surai et al 1998) are being replaced with synthetic ones that have been approved as additives to feeding mixtures for laying hens (Act No. 91/1996;Act No.…”
mentioning
confidence: 99%